A familial case of pseudohypoaldosteronism type II (PHA2) with a novel mutation (D564N) in the acidic motif in WNK4. Issue 6 (1st May 2019) - Sakoh, Takashi; Sekine, Akinari; Mori, Takayasu; Mizuno, Hiroki; Kawada, Masahiro; Hiramatsu, Rikako; Hasegawa, Eiko; Hayami, Noriko; Yamanouchi, Masayuki; Suwabe, Tatsuya; Sawa, Naoki; Ubara, Yoshifumi; et al.
Abstract: Background: There have been still few case reports of pseudohypoaldosteronism type II (PHA2), also known as Gordon's syndrome, genetically diagnosed, and this is the first report of familial PHA2 case in Japan with a novel D564N mutation in WNK4 . Methods: A 29‐year‐old woman was admitted to our hospital due to hyperkalemia (serum potassium: 6.4 mmol/L). She had mild hypertension (135/91 mm Hg), a bicarbonate level at the lower limit of the normal range (HCO3 : 22 mmol/L) with a normal anion gap, low plasma renin activity (0.2 ng ml ‐1  hr ‐1 ), and high urinary calcium excretion (505.4 mg/g Cre). A hereditary condition was suspected because her mother also had the same symptoms. We performed a comprehensive genetic analysis for major inherited kidney diseases with next‐generation sequencing including the genes responsible for PHA2 ( WNK1, WNK4, KLHL3, and CUL3 ). Results: Genetic analysis revealed that the patient and her mother had a novel missense mutation (D564N) in the acidic motif in WNK4, which leads to the diagnosis of PHA2. Administration of trichlormethiazide (1 mg/day) effectively ameliorated her blood pressure (114/69 mm Hg), plasma bicarbonate (25 mmol/L), serum potassium (4.3 mmol/L), and urinary calcium excretion (27.2 mg/g Cre). Conclusion: We report the first Japanese familial case of PHA2 with WNK4 mutation. D564N mutation in WNK4 is a novel genetic cause of PHA2 with a relatively mild phenotype. Abstract : We report the first Japanese familial case of PHA2 with WNK4 mutation. D564N mutation in WNK4 is the novel genetic cause of PHA2 with relatively mild phenotypes.